Effects of film thickness on critical crack tip opening displacement in single-crystalline and polycrystalline submicron Cu films. (July 2016) - Hirakata, Hiroyuki; Yoshida, Takuya; Kondo, Toshiyuki; Minoshima, Kohji
Abstract: We performed in - situ field emission scanning electron microscopy fracture toughness tests on single-crystalline and polycrystalline submicron-thick Cu films. In all specimens, the notch root became blunt, and a crack was initiated from the blunted notch root. The critical crack tip opening displacement (CTOD) for crack initiation, δ i, was thickness dependent, where δ i decreased with a decrease in the thickness. The critical CTOD normalized by the thickness, δ i / B, values of the films were similar ( δ i / B  = 1.4–1.9), irrespective of the film thickness and microstructure. This suggested that the local fractures of the submicron Cu films were similar.